Evaluación del lactosuero dulce y pulpa liofilizada de mango (Mangifera indica L.) en una bebida láctea fermentada funcional - Montesdeoca Chávez, María Agustina (2020)
The objective of this research was to evaluate sweet whey and lyophilized mango pulp to produce a fermented milk drink with functional characteristics. The factors under study were: percentage of whey with levels of 50% and 60%, and percentage of freeze-dried mango pulp with levels of 1.5%, 1.75% and 2%. A Completely Random Design (DCA) was applied in a two-factor AxB arrangement, six treatments with three replicates each were studied. A 2kg base mix consisting of milk, whey, lyophilized mango pulp and ingredients such as sugar and lactic acid was used as an experimental unit. Functional characteristics, physicalchemical and sensory analyzes were evaluated using SPSS statistical program. Total polyphenols and antioxidant capacity presented statistically significant differences between treatments, establishing T3 (50% whey and 2% lyophilized mango pulp as best), on the other hand, the variables of viscosity and acidity placed T6 (60% whey and 2% freeze dried mango pulp) and T2 (50% whey and 1.75% freeze dried mango pulp) respectively. Sensory analysis was carried out using a affective test, evaluating five attributes (color, odor, flavor, consistency and acceptability), with a five-point hedonic scale, establishing T4 as the best treatment (60% whey and 1.50% lyophilized mango pulp), obtaining a fluid consistency drink with a pleasant smell and taste, classified as acceptable. The combination of 50% sweet whey and 2% freeze-dried mango pulp showed a drink with functional potential and favorable physico-chemical characteristics. The combination of 50% sweet whey and 2% freeze-dried mango pulp showed a drink with functional potential and favorable physico-chemical characteristics.